PREVALENCE OF INDONESIA’S ALCOHOL CONSUMPTION, RISK FACTORS, AND ITS CLUSTER MAPPING: AN ANALYSIS OF INDONESIA BASIC HEALTH SURVEY 2018 - Prisca Petty Arfines; Rika Rachmalina; Rofingatul Mubasyiroh; Tities Puspita; Fuska Atomita Restu Arfines (GIZI INDONESIA, 2022)
Excessive alcohol consumption increases the risk of non-communicable diseases. This study aimed to analyze the risk factors for alcohol consumption in Indonesia and present a cluster mapping based on the risk factors. The sample of this study was individuals aged 15 years and over who participated in the Indonesia Basic Health Survey 2018, while pregnancy was the exclusion criterion. The sample size for univariate was 542,682 individuals and 539,905 individuals in the multivariate analysis conducted using logistic regression. The prevalence of alcohol consumption was 3.7 percent. The risk factors for drinking alcohol included work as a farmer/fisherman/laborer or other manual occupations (aOR = 1.10; 95% CI 1.04-1.17), smoking (aOR = 4.93; 95% CI 4.62- 5.25), experiencing common-mental disorders (CMD) (aOR = 2.13; 95% CI 1.99-2.28), centrally obese (aOR = 1.21; 95% CI 1.13-1.3) and being overweight/obese (aOR = 1.07; 95% CI 1.01-1.13). On the other hand, the factors that showed a reduced risk of alcohol consumption were being the head of household (aOR = 0.79; 95% CI 0.74-0.85), low education level (aOR = 0.75; 95% CI 0.68-0.83), not working (aOR = 0.74; 95% CI 0.68-0.80), low socioeconomic status (aOR = 0.82; 95% CI 0.75-0.90), and being married (aOR = 0.56; 95% 0.52-0.61) or divorced (aOR = 0.60; 95% CI 0.53-0.67). Type of work as manual workers, smoking, experiencing CMD, being obese centrally, and overweight or generally obese are the main risk factors for alcohol consumption. Specific interventions are needed based on the risk factor cluster of alcohol drinkers